Distinguishing beyond-standard model effects in neutrino oscillation - A. Calatayud-Cadenillas; A. Pérez-G; A.M. Gago (Physics Letters B)
We systematically assess the DUNE experiment's ability to distinguish between various beyond-standard neutrino oscillation hypotheses pair combinations. For a pair comparison, we evaluate the statistical separation, where one hypothesis plays the role of the true signal while the other corresponds to the test signal. The beyond-standard neutrino oscillation hypotheses under scrutiny include neutrino decay (invisible and visible), non-standard inter-actions, quantum decoherence, and the violation of the equivalence principle. We found that the violation of the equivalence principle is the easiest to differentiate compared to the rest of the hypotheses. Additionally, from our χ2 statistical separation test, we investigate potential discrepancies between the measured CP-violation phase δCP, θ23, and Δm312 relative to their respective true values, which could occur for a given comparison. In our analysis, we will take the true values of δCP as 90∘ and 180∘, while θ23 and Δm312 are fixed in its global fit values. In particular, even in cases where the scenarios of beyond-standard neutrino oscillation hypotheses are statistically indistinguishable, the measured values can exhibit significant deviations from their true values.